CHANGES IN THE LEVEL OF PHYSICAL TRAINING OF YOUNG BASKETBALL PLAYERS AND STREET PLAYERS DURING TRAINING. - Abdualimov Rufat Uchqun o’g’li (Galaxy International Interdisciplinary Research Journal, 2023)
The glittering curriculum for changes in the technical, tactical and game preparation volume during annual training with basketball and streetball is seen as a backup to improve the physical efficiency of adolescents